Muscle oxygenation and energy substrate utilization in 200m and 500m sprint - Jardsakul, P.; Senakham, N.; Ratchanavy, P.; Khamros, W.; Senakham, T. (Journal of Physical Education and Sport, 2024)
The presence of oxygen in active muscles dictates substrate metabolism which is crucial for sport performance. However, it`s information in dragon boat races is limited. This study aimed to evaluate muscle oxygenation and energy substrate utilization during 200-m and 500-m dragon boat races among elite athletes. Ten male dragon boat athletes participating in international competitions (age 26.60 ± 3.20 years, weight 79.54 ± 3.36 kg, height 174.80 ± 5.67 cm) completed 200-m and 500-m simulated race trials on an ergometer in a randomized, counterbalance, crossover fashion, with a 2-day separation. Near-infrared spectroscopy (NIRS) monitors were placed on the biceps brachii (BB) and latissimus dorsi (LD) to investigate tissue saturation index (TSI), oxyhemoglobin concentration (O2Hb), deoxyhemoglobin concentration (HHb), and total hemoglobin (tHB) during the trials, and gas analyzer was employed to evaluate energy substrate utilization. The results revealed that during 200-m and 500-m races, TSI, O2Hb, and tHb in the BB significantly decreased (P<0.05), whereas HHb significantly increased (P<0.05). In the LD, this change was observed only in 200-m race (P<0.05). When comparing between the distances, all oxygen parameters in the BB were significantly higher in 500-m than 200-m (P<0.05), while in the LD, TSI, O2HB, and tHb were significantly higher (P<0.05). Total energy and energy from carbohydrate were also significantly higher in 500-m than 200-m race (P<0.01). The results of this study indicate that there is difference in muscle oxygenation and energy substrate expenditure during 200-m and 500-m dragon boat races. This disparity may be resulted from different muscle recruitment patterns, as indicated by difference in oxygen parameters in the BB and LD during the races. This study provides new knowledge to the area of paddle sports and offers practical insights that can help coaches and related persons to optimize athletic performance during training and competitions. More researches are required to clarify the mechanisms underlying the differences in muscle oxygenation in different dragon boat race distances.